Whole-body magnetic resonance imaging in inflammatory diseases: Where are we now? Results of an International Survey by the European Society of Musculoskeletal Radiology. Issue 136 (March 2021) - Giraudo, Chiara; Lecouvet, Frederic E.; Cotten, Anne; Eshed, Iris; Jans, Lennart; Jurik, Anne Grethe; Maas, Mario; Weber, Michael; Sudoł-Szopińska, Iwona
Highlights: WB-MRI is still not routinely applied for musculoskeletal inflammatory diseases. Myositis is the most frequent WB-MRI indication in adults. CRMO is the most common WB-MRI indication in children. WB-MRI protocols' optimization is needed. Abstract: Purpose: To investigate the current role of WB-MRI for rheumatic inflammatory diseases in clinical practice using a survey addressed to musculoskeletal radiologists. Methods: A survey composed of 61 questions, subdivided in three sections, demographics (five questions), application of WB-MRI for inflammatory musculoskeletal diseases in adults and children (28 questions: 7 open and 21 multiple choice for each subgroup) was distributed via the European Society of Musculoskeletal Radiology (ESSR) from July 2 to December 31, 2018 to radiologists working in academic, private, and public workplaces. Comparisons among the different workplaces were performed using the Chi-squared and the Kruskal-Wallis test for nominal and ordinal data, respectively (p < 0.05). Results: Seventy-two participants out of the 1779 (4%) members of the ESSR with 10.4 ± 7.9 years of experience in musculoskeletal imaging, replied to at least one question. 30.6% and 12.3% of the respondents performed at least 50 WB-MRI examinations per year in adults and children, respectively. The most frequent indications were myositis in adults and chronic recurrent multifocal osteomyelitis (CRMO) in children, the latter mostly in academic centers (p = 0.013). The ESSR Arthrits Subcommitte's protocol was applied by half of the participants and especially radiologists working in private practice used it for adults (p = 0.025). Contrast medium was rarely used for adults particularly by academics (p = 0.04). Diffusion Weighted Imaging was applied for children mostly in private practice (p = 0.01) although, overall, it plays a marginal role. Scoring systems were rarely used. Ongoing research is limited. Conclusion: WB-MRI is not routinely applied for musculoskeletal inflammatory diseases. The most frequent indications are myositis and CRMO.